Fabrication and flexural experimentation of composite sandwich beams with metal facesheets - Tan, Druce Chow Yeow (Nanyang Technological University, 2024)
This study investigates the bending response of the sandwich composite beam that has undergone three-point bending. The sandwich composite consists of a Unifoam Polystyrene core sandwiched between two aluminum facesheets. This project will be going through the fabrication process of the sandwich composite beam, experimental set-up for testing various specimens, and experimental results of the three-point bending test and compression test. Firstly, unifoam beams with various spans undergo 3-point bending until they fracture to calculate the accurate material properties of the unifoam material that is not commercially available online. Secondly, aluminum facesheet beams also undergo 3-point bending until it reaches a plateau to study their ductile behavior. Next, the sandwich composite beam undergoes 3-point bending until failure to study its bending behavior, the beam fails by core indentation due to localized force. Therefore, a compression test is conducted on the unifoam core to obtain its compressive behavior and understand the different phases of compression.